PENERAPAN ASAS KEADILAN DALAM PELAKSANAAN PEMBERIAN PERIZINAN MINIMARKET PADA DINAS PENANAMAN MODAL DAN PELAYANAN TERPADU SATU PINTU (DPM-PTSP) KOTA PALEMBANG - Seftiyani, Layla Tri; Fauziah, Fauziah; Mursid, Fadillah (Program Studi Muamalah Fakultas Syariah dan Hukum, 2021)
ABSTRACT In general, a license requires a principle of justice in its application so that no onefeels burdened in its implementation. The problems in this study are 1) How is theimplementation of the establishment of a minimarket around which there are traditionalmarkets and stalls / shops by the Department of Investment and One Stop IntegratedService (DPM-PTSP) Palembang City? 2) How is the ef ect of the principle of justice onthe licensing of minimarkets around which there are traditional markets and stalls / shopsby the Palembang City Investment Service and One Stop Integrated Service (DPM-PTSP)? This type of research is field research (field research), meaning that the source ofthe data used as a reference in research related to the object of this thesis research, themethod used in this research is descriptive qualitative. The data source used consists ofthree data sources, the first is primary data sources by conducting interviews anddocumentation. Secondary data such as data obtained from books, scientific papers,literature studies. Tertiary data obtained from articles, internet, dictionaries. Based on the results of the research, it can be concluded that, first, in granting aminimarket licensing at the Palembang City Investment and One Stop Services Service(DPM-PTSP) based on the Mayor of Palembang Regulation No. 25 of 2011 concerningGuidelines for the Arrangement and Development of Shopping Centers and ModernStores. Article 12 paragraph (2). In the Regulation of the Mayor of Palembang No. 25 of2011 Article 3 paragraph (9) letter e explains that the establishment of a mini-market thatis either independent or integrated with shopping centers or other buildings must payattention to the existence of traditional markets and stalls / shops in the surrounding areathat are smaller than the minimarket.Second, in the implementation of licensing for minimarkets, they still do not apply the principle of justice because there are still many minimarkets that are close to traditional markets and stalls / shops so that there iscompetition and can cause reduced income for small business owners who are near theminimarket.Key words: Principles of Justice, Minimarket Licen